Genetics Evaluation of Targeted Exome Sequencing in 223 Chinese Probands With Genetic Skeletal Dysplasias - Lv, Shanshan; Zhao, Jiao; Xi, Lei; Lin, Xiaoyun; Wang, Chun; Yue, Hua; Gu, Jiemei; Hu, Weiwei; Fu, Wenzhen; Wei, Zhanying; Zhang, Hao; Hu, Yunqiu; et al. (Frontiers in Cell and Developmental Biology, 2021)
Genetic skeletal dysplasias (GSD) are a type of disease with complex phenotype and high heterogeneity, characterized by cartilage and bone growth abnormalities. The variable phenotypes of genetic skeletal dysplasia (GSD) make clinical diagnosis difficult. To explore the clinical utility of targeted exome sequencing (TES) in the diagnosis of GSD. 223 probands with suspected GSD were enrolled for TES with a panel of 322 known disease-causing genes. After bioinformatics analysis, all candidate variants were prioritized by pathogenicity. Sanger sequencing was used to verify candidate variants in the probands and parents and to trace the source of mutations in family members. We identified the molecular diagnoses for 110/223 probands from 24 skeletal disorder groups and confirmed 129 pathogenic/likely pathogenic variants in 48 genes. The overall diagnostic rate was 49%. The molecular diagnostic results modified the diagnosis in 25% of the probands, among which mucopolysaccharidosis and spondylo-epi-metaphyseal dysplasias were more likely to be misdiagnosed. Also improved the clinical management of 33% of the probands; 21 families received genetic counseling; 4 families accepted prenatal genetic diagnosis, one of them was detected to carry pathogenic variants. The results showed that TES achieved a high diagnostic rate for GSD, helping clinicians confirm patients’ molecular diagnoses, formulate treatment directions and carry out genetic counseling. TES could be an economical diagnostic method for patients with GSD.